INTERRELIGIOUS HARMONIZATION (ANALYTIC STUDY OF KALICINTA VILLAGE, KOTABUMI, LAMPUNG) - Susanto, Roni; Rohmah, Wahidatur; Hidayanti, Sanita Nur; Sugiyar, Sugiyar (IAIN PONOROGO, 2023)
This research is motivated by the harmonization of inter-religious communities in Lampung province. The harmonization of religious communities is evidenced by the Islamic community's cultural activities involving Christians. This phenomenon is in the village of Kalicinta, Kotabumi district, Lampung province. This research discusses the analysis of the harmonization of religious communities in Kalicinta Village, Kotabumi, and Lampung. The research method uses a qualitative research approach. The source of data consists of primary and secondary data. Primary data was obtained by observing and interviewing ten informants consisting of four village officials and six communities. Secondary data sources were obtained from related articles. The analytical method used data reduction, data display, and conclusion. The results of the study found that: (1) the Kalicinta village community has a high tolerance attitude in maintaining inter-religious harmonity (2) the Kalicinta village community understands exclusivism in the theological realm and inclusivism in the social realm. Research ini di latar belakangi oleh harmonisasi antar umat beragama yang berada di provinsi Lampung. Harmonisasi umat beragama di dibuktikan dengan aktivitas budaya masyarakat Islam yang melibatkan warga kristiani. Fenomena ini berada di desa Kalicinta, kabupaten Kotabumi provinsi Lampung. Research ini membahas tentang analisis harmonisasi umat beragama di desa kalicinta kotabumi lampung. Metode penelitian menggunakan pendekatan penelitian kualitatif. Sumber data terdiri dari data primer dan sekunder. Data primer diperoleh dengan observasi dan wawancara sepuluh informan yang terdiri dari empat perangkat desa dan enam masyarakat. Sumber data sekunder diperoleh dari artikel-artikel yang terkait. Metode analisis yang digunakan adalah data reduksi, data display, dan penarikan kesimpulan. Hasil penelitian menemukan bahwa : (1) masyakarat desa Kalicinta memiliki sikap toleransi yang tinggi dalam menjaga keharmonisan dan kerukunan, (2) Masyarakat desa kalicinta ber-faham esklusivisme pada ranah teologi dan inklusivisme pada ranah sosial.